The Brazilian version of the Childhood Health Assessment Questionnaire (CHAQ) and the Child Health Questionnaire (CHQ) - Machado, C. S M [UNESP]; Ruperto, N.; Silva, C. H M; Ferriani, V. P L; Roscoe, I.; Campos, L. M A; Oliveira, S. K F; Kiss, M. H B; Bica, B. E R G; Sztajnbok, F.; Len, C. A.; Melo-Gomes, J. A. (My University, 2001)
We report the cross-cultural adaptation and validation into Brazilian-Portuguese of the parent's version of two health related quality of life instruments. The Childhood Health Assessment Questionnaire (CHAQ) is a disease specific health instrument that measures functional ability in daily living activities in children with juvenile idiopathic arthritis (JIA). The Child Health Questionnaire (CHQ) is a generic health instrument designed to capture the physical and psychosocial well-being of children regardless the underlying disease. The Brazilian CHAQ was revalidated, while the CHQ has been derived from the Portuguese version. A total of 471 subjects were enrolled: 157 patients with JIA (27% systemic onset, 38% polyarticular onset, 9% extended oligoarticular subtype, and 26% persistent oligoarticular subtype) and 314 healthy children. The CHAQ discriminated clinically healthy subjects from JIA patients, with the systemic, polyarticular and extended oligoarticular subtypes having a higher degree of disability, pain, and lower overall well-being scores when compared to their healthy peers. Also the CHQ discriminated clinically healthy subjects from JIA patients, with the systemic onset, polyarticular onset and extended oligoarticular subtypes having a lower physical and psychosocial well-being score when compared to their healthy peers. In conclusion the Brazilian versions of the CHAQ-CHQ are reliable and valid tools for the combined physical and psychosocial assessment of children with JIA. © Copyright Clinical and Experimental Rheumatology 2001.
Keywords: Brazilian Child Health Questionnaire (CHQ); Brazilian Childhood Health Assessment Questionnaire (CHAQ); Cross cultural adaptation and psychometric evaluation; Health related quality of life; Healthy children; Juvenile idiopathic arthritis (JIA); Brazil; child; cultural factor; disability; female; health status; human; juvenile rheumatoid arthritis; language; male; psychometry; quality of life; questionnaire; reproducibility; validation study; Arthritis, Juvenile Rheumatoid; Child; Cross-Cultural Comparison; Cultural Characteristics; Disability Evaluation; Female; Health Status; Humans; Language; Male; Psychometrics; Quality of Life; Questionnaires; Reproducibility of Results